Development of Porous Polysaccharides-Hydroxyapatite Composite Scaffolds via Freeze Drying Method and in vitro Osteoconductivity on MG 63 Cells - Rajesh, R.; Kumar, S.K. Ashok; Kenie, Dunkana Negussa; Ravichandran, Y. Dominic (Asian Journal of Chemistry, 2017)
Tricomponent scaffolds of hydroxyapatite (HAP) with a mixture of polysaccharides have been prepared by freeze drying method and TG, FTIR, XRD and FE-SEM. FTIR and powder XRD analysis were confirmed the formation of composites with strong electrostatic interactions. FE-SEM images showed the porous morphology of the prepared tricomponent scaffolds. The cell proliferation and mineralization of the scaffolds were evaluated through in vitro MTT assay and alkaline phosphatase activity on MG 63 cell line. The study proved that the prepared tricomponent scaffolds have better cell proliferation and mineralization. Moreover, the well dispersion and adhesion of cells on to the scaffolds were evident from the dye stained fluorescent microscopic images. Porosity of the prepared tricomponent scaffolds plays a vital role, which is well corroborated from the higher cell proliferation and mineralization of chitosan/gellan-HAP scaffold. The viscosity and porosity of the scaffolds play a crucial role on the compressive strength of prepared scaffolds.